2022
DOI: 10.3389/fendo.2022.965290
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between indices of circulating blood cells and bone homeostasis in osteoporosis

Abstract: Bone development have been shown to play an important role in regulating hematopoiesis as one major component of bone marrow microenvironment. Recent studies support the notion that there is an intricate relationship between hematopoiesis and bone homeostasis, however, little is known about the alterations in the hematopoietic lineages in pathologic conditions. Using various osteoporotic mouse models, we show here that bone microarchitecture abnormalities alter parameters of peripheral blood cells. The level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…These data are consistent with the literature. Recently, Li et al [19] investigated a large cohort of osteoporotic patients and healthy subjects (more than 1100 people in total) and reported higher white blood cell, neutrophil and monocyte counts in cases than in controls. These results were con rmed even when the analysis was restricted to men (about 6% of this population).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data are consistent with the literature. Recently, Li et al [19] investigated a large cohort of osteoporotic patients and healthy subjects (more than 1100 people in total) and reported higher white blood cell, neutrophil and monocyte counts in cases than in controls. These results were con rmed even when the analysis was restricted to men (about 6% of this population).…”
Section: Discussionmentioning
confidence: 99%
“…Speci cally, a close and complex interaction between the immune system and cells involved in bone remodelling has emerged, leading to the genesis of the eld of osteoimmunology [27]. Many factors including immune cells, glutamate signalling, mesenchymal stromal cells, and endothelial cells, play a crucial role in bone homeostasis and thus in osteoporosis [19,[28][29][30]. Non-metastatic [ 18 F]PSMA-1007 bone uptake might be the result of bone remodelling typical of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately one-third of postmenopausal women aged > 50 years are affected by OP. As the population ages, the incidence of osteoporotic fractures increases [19]. Growing evidence has suggested that systematic diseases such as diabetes and rheumatic inflammatory diseases are strongly associated with the development of OP [20,21].…”
Section: Oxidative Stress In Menopausal Women Elderly Patients and Di...mentioning
confidence: 99%
“…Bone marrow mesenchymal stem cells (BMSCs) are non-hematopoietic stem cells and progenitor cells that have the potential to differentiate into various cell types, including osteoblasts, adipocytes, and chondrocytes ( 1 , 2 ). BMSCs are characterized by their abundance, high capacity for self-renewal, pluripotency, weak immunogenicity, and ease of transfection ( 3 ), which makes them as an ideal source of stem cells for transplantation and they are broadly used for the treatment of bone-related diseases ( 4 ).…”
Section: Introductionmentioning
confidence: 99%